COMPUTER USE AS A 486-DX PC ROUTER AND WITH LINUX FREESCO FIREWALL - Erwin Gunawan; Fivtatianti Hendajani, SKom, MM (Jurnal Sistem Komputer, 2005)
Basically creativity into something very important, when the technology changes so quickly. 486-DX computer for example, who used to be proud of now no more than an old machine that is more worthy of display company warehouses. Linux c omes with a very creative solution. 468-DX computer use conjured up a router is a reliable PC. DHCP server, firewall, FTP servers, Telnet servers and other capabilities can be done with Freesco without time-consuming and high cost.  And that is not unlawful passi .